Characteristic of Surface Geometry of the Seersucker Woven Fabrics - Matusiak, Małgorzata (Wydawnictwo Politechniki Łódzkiej, 2025)
The seersucker woven fabrics are three-dimensional fabrics characterised by a presence of the puckered strips, mostly in the warp direction. The seersucker effect, associated with the specific shape of the fabric surface, affects the surface properties of fabrics, especially the geometric structure of their surface. In the presented work the surface geometry of two variants of the seersucker woven fabrics were measured using the non-contact – optical method by means of the MicroSpy® Profile profilometer co-operating with the specialist Mark III software. On the basis of data from the profilometer the parameters and functions characterising the geometric structure of fabrics’ surface were determined and analysed for the entire surface of fabric samples as well as separately for the puckered and flat areas of the fabrics. Obtained results showed that the non-contact optical method using the profilometer provides data which allow for comprehensive characterization of surface geometry of the seersucker effect. Additionally, by comparison of the surface geometry parameters for the puckered and flat areas of the seersucker woven fabrics it is possible to quantify the seersucker effect.
Keywords: seersucker woven fabrics; surface geometry; roughness; waviness; profilometer; measurement; tkaniny seersucker; geometria powierzchni; chropowatość; falistość; profilometr; pomiar